DESIGN AND DYNAMIC ANALYSIS OF A NEW CHAOTIC VIBRATING SCREEN - WANG ChengJun; ZHU Tao (Jixie qiangdu)
Aiming at the problems of single movement dimension of traditional vibrating screen, low screening efficiency, short life of key parts, etc. Using the randomness of chaotic vibration and the characteristics of reciprocating non-periodic motion, chaotic vibration is applied to the vibrating screen to improve the screening efficiency. A new type of chaotic vibrating screen with one redundant degree of freedom is developed, the dynamic model of the new chaotic vibrating screen is established, the vibration differential equation of the vibrating screen is obtained by the Lagrange method, and its dynamic characteristic diagram is obtained through simulink simulation analysis. Chaotic identification is performed on the time-frequency diagram, phase diagram, Poincare map and Lyapunov exponent diagram obtained from the simulation results. The simulation shows that the Poincre map of the chaotic vibrating screen is scattered and the maximum Lyapunov exponent is positive. The motion output of the new chaotic vibrating screen is chaos Vibration, the research results of the thesis can provide a theoretical basis for the design and application of chaotic vibrating screens.